Association between long-term pulse pressure trajectories and risk of end-stage renal diseases in incident malignant hypertensive nephropathy: a cohort study. Issue 1 (4th August 2020) - Zhuang, Yi; Ding, Caiyan; Xu, Yajing; Ding, Zhongqin; Yu, Dahai
Abstract : Objective: The trajectories of pulse pressure (PP) might affect the prognosis of malignant hypertensive nephropathy (MHN). We aimed to describe the association between PP trajectories and the future risk of end-stage renal disease and to identify and compare the associated patient characteristics of any distinct trajectory patterns in MHN patients. Methods: Patients with newly diagnosed biopsy-proven MHN 2010–2015 were included. Latent class growth analysis was applied to the PP measured over 3 years prior to biopsy to identify distinct trajectories. Concurrent systolic blood pressure, diastolic blood pressure, plasma creatinine, and 24-h urine protein measurements for each trajectory group were modelled using generalized estimating equations. The risk of end-stage renal disease (with kidney replacement therapy as a proxy) was estimated using Logistic regression. Results: Two hundred three patients were included (median-age 34 years, and 19.7% female). A two-group cubic model was optimal, with trajectories distinguished by the rate of PP and absolute level at final measurement. Trajectory Group-1 ( n  = 84) was characterized by 'first-increased-then-decreased' PP and trajectory Group-2 ( n  = 119) was characterized by 'first-decreased-then-increased' PP over 3 years prior to biopsy. Systolic and diastolic blood pressures, plasma creatinine, and 24-h urine protein were differed by the trajectory group. Baseline characteristics differed substantially between trajectory groups. Compared with Group-1, Group-2 had a 66% greater risk of developing into end-stage renal disease in the subsequent 3 years. Conclusions: Two distinct 3-year trajectories for PP exist with MHN. Early introduction of intensive antihypertensive treatment might delay the development of end-stage renal disease among patients with malignant hypertension.